Studies on woloszynskioid dinoflagellates VIII: life cycle, resting cyst morphology and phylogeny of Tovellia rinoi sp. nov. (Dinophyceae). Issue 5 (1st September 2017) - Pandeirada, Mariana S.; Craveiro, Sandra C.; Daugbjerg, Niels; Moestrup, Øjvind; Calado, António J.
Abstract: Tovellia rinoi nov. sp . is described on the basis of light microscopic and scanning electron microscopic examination of motile cells and resting cysts and the phylogenetic analysis of partial sequences of the large subunit ribosomal rRNA gene. The species was isolated from a flooded area near Aveiro, Portugal, and followed in culture through all stages of the life cycle, including formation of vegetative cells and gametes, sexual fusion, planozygote division through division cysts and the production of resting cysts. Motile cells had an ovate-conical epicone and a truncated or slightly excavated hypocone and were a little flattened dorsoventrally. Cell length was mostly 9–19 μm, the smaller cells less pigmented and with the potential to act as gametes but also capable of vegetative multiplication. The amphiesma had three series of vesicles on the epicone, one in the cingulum and two on the hypocone and an apical line of plates (ALP) oriented almost dorsoventrally across the cell apex. One vesicle separated the ALP from the cingulum on the ventral side, two on the dorsal side. The resting cysts, showing an equatorial constriction and densely covered by hair-like spines, represented a new type within the family Tovelliaceae. The new species formed a well-supported sister group to the other Tovellia species in a LSU rDNA–derived phylogeny. Sexual fusion started with gametic contact within 'dancing groups' of small cells. The initial contact on the mid-ventral side of both gametes was often visible as a hyaline bridge, which apparently involved a globular structure protruding from the ventral ridge of one or both gametes. The two gametes in a fusing pair behaved differently, with one gamete rotating as it fused into its partner until gametic eyespots merged and the gametic longitudinal flagella assumed the position of the paired longitudinal flagella of the planozygote. Resting cysts developed from large cells morphologically identifiable as planozygotes, with cyst spines growing rapidly. Conversion of planozygotes into division cysts that produced motile cells was also observed. Germinating cysts produced regularly two motile cells, each apparently with a single longitudinal flagellum. Nuclear cyclosis was not detected at any stage of the life cycle.